Blockchain Technology in Logistics and Supply Chain Management A Bibliometric and Co-Citation Analysis - Seelaboyina Radha; Govindaraj Manoj; Ratna Sirisha M.; Sathyakala S.; Rashid Syed Zahidur; Vigneshwaran K.S. (ITM Web of Conferences)
Just be sure that you are not giving advice that could backfire if seen in the wrong way, it is a great way to boost your reputation and gain people as followers. But existing studies point out major meagre adoption, high computational cost, low interoperability, privacy concerns, and energy inefficiencies as major challenges. Therefore, this study proposes a next-generation blockchain framework to overcome existing limitations by employing hybrid blockchain models, privacy-preserving techniques, energy-efficient consensus mechanisms, and adaptive smart contracts. Additionally, the research presents a cross-platform interoperability model to integrate blockchain with any enterprise resource planning (ERP) systems, Internet of Things (IoT) networks, and cloud logistics infrastructure in a seamless manner. Similarly, AI-assisted smart contracts and scalable blockchain architecture are suggested to improve supply chain management with realtime transaction capabilities. Through an examination of successful and failure cases in the blockchain domain, the study suggests a risk-mitigation framework, followed by a strategic roadmap for organizations to navigate through the bottlenecks towards adoption. The solutions proposed support economic feasibility, meet international standards and allow for a more resilient supply chain, making blockchain a viable solution to some of the pressures modern logistics faces.